Explanation of tourism capabilities and management for geosites on based assessment method of geodiversity sites - SOMAIE Jahantigh; Amir Karam; Ezatollah Ghanavati (تحقیقات کاربردی علوم جغرافیایی)
Geotourism is kind of responsible tourism with the aim of socio - economic development and strengthening of the scientific tourism destinations and tourism geological locations that emphasizes the protection of the heritage of the land and people of Sciences. Requires the development of a geo-tourism destination is recognizing its value and capability concept and planning barriers and providing favorable to its management. Tourism zone of Tangeh Vashi in the city of Firouzkoh, with different geological phenomena and scientific and complementary values, ​​is geotourism destination in local and sometimes national level. Therefore, in this study, using a variety of assessment methods geotourism area of ​​land that was presented in 2015 by Brill. In this, steps were taken. Therefore, the optimum user Tangeh Vashi Tourism, Economic User scientific approach - protective. The results shows that in generally, Tangeh Vashi has suitable condition in educational and tourism values. Also, Risk of collapse in Tangeh Vashi is relatively high. According to the results, the optimal management of geotourism Tange Vashi, the powers of access and the center of the province's population and strengthening of the complementary and diversity of geological and strengthen tourism and the preservation interpretation capability along with the application the physical protection and promotion of scientific partnership rural and legal controls.